Transient fault detection and location in power distribution network: A review of current practices and challenges in Malaysia - Asman S.H.; Ab Aziz N.F.; Ungku Amirulddin U.A.; Ab Kadir M.Z.A. (MDPI AG, 2023)
Electric power system protection; Losses; Monitoring; Power quality; Signal processing; Current practices; Fault interactions; Power distribution network; Power distribution system; Protection systems; Recommended practice; Remote supervision; Transient-fault detection; Fault detection